Kearifan Lokal Hamis Batar Suku Manehitu Fafiur Di Kabupaten Belu NTT - Frida Tahu; Augusta De Jesus Magalhaes (Indonesian Journal Publisher, 2020)
This research aimed to find outthe mechanism of hamisbatar local wisdom of ManehituFafiur Tribe, in Belu Regency, NTT. This study was descriptive qualitative research. Data collection was carried out using observation, documentation and interview. Data analysis was conducted qualitatively encompassing data reduction, data display, and conclusion drawing. The result of research showed that hamisbatarrite was organized in six stages: preparing land rite, planting rite, hamisbatarrite held in Manehitufafiur tribal house, corn harvest rite, corn collection in customary house, and corn binding rite still continue to be implemented until today.